Prediction of Counter-Arguments using Indian Logic - Mahalakshmi, G. S.; Geetha, T. V. (INFOCOMP Journal of Computer Science, 2009)
Argument gaming is a process where arguments and counter-arguments are exchanged as moves and counter-moves during rational discussions. Predicting the direction of argumentation will facilitate the arguer to contribute to a maximum, if the objective of argumentation is knowledge sharing. In this paper, we propose an algorithm for prediction of counter-arguments during argumentative discussions by utilizing the system of syllogistic inference of Indian philosophy. In other words, this is a means to silently track the counter-moves of the opponent for every move from the proponent.